Underwater drone for marine ecosystem applications: An alternative propulsion and control system - Paulsen, Lachlan (Wellington Faculty of Engineering Symposium, 2023)
Aotearoa New Zealand’s coastal marine environments are vital natural assets, intertwined with tourism, the economy, and the nation’s identity. These coastal ecosystems face multiple threats, necessitating efficient monitoring methods. However, various debris such as kelp makes traversal of these environments difficult for craft using conventional propeller propulsion, which is prone to getting tangled up in such debris. The aim of this project was to explore an alternative propulsion system for coastal monitoring, specifically the use of a novel waterjet propulsion system for a Remote Operated Underwater Vehicle (ROUV). This was accomplished by the development of a ROUV prototype utilizing a waterjet propulsion system. A dual layer propulsion system was created that uses solenoid valves to redirect the flow of water from a central pump to external nozzles for movement and orientation. The prototype drone was then completed by fitting the propulsion system into a watertight container. The viability of this propulsion method was assessed by whether the movement of the ROUV has three degrees of freedom, and whether or not it can achieve a top speed greater than 1 meter per second in a tank of water. The development of this prototype ROUV with a waterjet propulsion system will ideally inform the design of a full-scale AUV prototype, which will revolutionize the monitoring of the precious coastal ecosystems to safeguard them for future generations.